Baryons in the Cosmic Web of IllustrisTNG - I: gas in knots, filaments, sheets, and voids - Martizzi, Davide; Pillepich, Annalisa; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We analyse the IllustrisTNG simulations to study the mass, volume fraction, and phase distribution of gaseous baryons embedded in the knots, filament
Gesehen am 31.05.2019